Role of Physical and Cognitive Factors in Passing Abilities of Futsal Athletes in Universitas Padjadjaran - Lubis, Leonardo; Muhammad, Afan Maulana; Nandina, Oktavia (Majalah Kedokteran Bandung, 2019)
Futsal is a variation of soccer, to be played on a smaller field, with the fastest development among other indoor sports. Futsal players need to master several basic playing techniques to be able to play good futsal, one of them is passing. There are 2 factors that affect futsal athlete skills; physical and mental factors, including cognitive factors. This study aimed to determine the contribution of physical and cognitive factors on the ability to execute passing techniques. A cross-sectional analytic study was conducted in October 2018 on 33 participants who were listed as futsal players in the Faculty of Medicine Futsal Unit, Universitas Padjadjaran, and in the amateur futsal club, La Coruna FC. Physical factor data consisting of body muscle mass percentage, leg muscle percentage, total body fat percentage, and legs subcutaneous fat percentage were measured using Body Impedance Analysis tool while the cognitive factors consisting of; attention, short term memory, and spatial ability, were measured using grid concentration test, digit span test, and spatial ability test, respectively. Athlete’s passing ability was measured using 30 second pass and stop test. Data were then analyzed using regression analysis. The results showed that the percentage of leg muscles has the highest significance value for the athlete’s passing ability. (β=0.6, p<0.05) while the leg muscles percentage and attention level are shown to be the physical and cognitive factors which play greater roles in the passing ability of futsal athletes.Peran Faktor Fisik dan Kognitif  terhadap Performa Teknik Dasar Passing Atlet Futsal Universitas Padjadjaran Futsal adalah variasi sepakbola yang dimainkan di lapangan yang lebih kecil. Atlet futsal perlu menguasai beberapa teknik bermain dasar untuk bermain futsal dan salah satunya adalah passing. Ada 2 faktor yang memengaruhi keterampilan atlet futsal, yaitu fisik dan mental yang salah satunya adalah kognitif. Penelitian ini bertujuan mengetahui kontribusi faktor fisik dan kognitif terhadap kemampuan teknik passing. Studi analitik cross-sectional dilakukan terhadap 33 peserta yang terdiri dari atlet futsal Fakultas Kedokteran dan atlet futsal klub amatir, La Coruna FC selama Oktober 2018 di Jatinangor. Data komponen fisik terdiri atas persentase massa otot tubuh, persentase otot tungkai, persentase lemak tubuh total, dan persentase lemak subkutan kaki yang diukur dengan alat analisis impedansi tubuh, sedangkan kognitif terdiri atas konsentrasi, memori jangka pendek, dan kemampuan spasial yang masing-masing diukur dengan uji konsentrasi grid, uji rentang digit, dan uji kemampuan spasial. Kemampuan passing diukur menggunakan tes pass and stop selama 30 detik. Data kemudian diproses dengan analisis regresi. Hasil Analisis regresi menunjukkan persentase otot kaki memiliki nilai signifikansi tertinggi untuk kemampuan passing atlet. (β=0,6, p<0,05). Persentase otot tungkai dan tingkat konsentrasi adalah faktor fisik dan kognitif yang memiliki peran lebih besar dalam kemampuan passing atlet futsal Jatinangor.